Implementation of the IPA Method in Patient Satisfaction Services at the Dr. Komang Makes Indonesian Navy Hospital, Website-Based - Purwopeni, Listyowati; Indriani, Ulfah (Jurnal ICT : Information and Communication Technologies, 2025)
Hospitals play a crucial role in providing high-quality healthcare services, particularly for inpatients who require intensive and continuous care. However, gaps often exist between patient expectations and perceived service performance, leading to dissatisfaction and inefficiencies in hospital operations. This study aims to evaluate the quality of inpatient services at Dr. Komang Makes Indonesian Navy Hospital using the Importance Performance Analysis (IPA) method to identify priority areas for improvement. The research employed both library and field studies, including observations, interviews, and questionnaires distributed to 100 inpatients. Data were analyzed by calculating performance and expectation scores across five service quality dimensions—reliability, assurance, responsiveness, empathy, and tangibility—to determine satisfaction levels. The findings revealed an average satisfaction index of 1.01, indicating that overall inpatient services are satisfactory, particularly in the assurance, empathy, and tangible dimensions. However, the reliability and responsiveness dimensions showed notable performance gaps, especially concerning doctor visit schedules, clarity of procedures, and response to patient complaints. These results highlight the need for targeted interventions, such as enhancing digital integration, improving communication systems, and increasing staff responsiveness. The implementation of continuous IPA-based evaluations is recommended to support systematic quality improvement and strengthen patient trust. This study contributes to the development of a patient-centered, technology-driven service model that enhances healthcare quality and organizational performance at Dr. Komang Makes Indonesian Navy Hospital.